Contrasting Multiple Choice and Cloze Task on Student’s Reading Comprehension - Elyza Martiarini (Deiksis, 2017)
The objective of this research is to obtain an empirical data about contrasting student’s reading comprehension by using two types of tests: Multiple Choice and Cloze Task. The research type was a comparative descriptive method. The subject consisted of 30 students of the fourth semester of English Department at University of Indraprasta PGRI in 2015-2016 academic year. The research data were collected by using pre-test and post-test. The result of data cultivation identified that based on test by using Multiple Choice, the average score (mean) was 69.3, median was 64.49, mode was 62.1, and deviation standard was 13.40. Whereas Cloze Task mean was 55.6, median was 52.86, mode was 50, and deviation standard was 9.97. On the basis of hypothesis test, ttest 15.56 was higher than ttable 1.67. It assumed that the significance result both Multiple Choice and Cloze Task are different (contrastive), in which student’s reading comprehension by Multiple Choice was higher than Cloze Task.Keywords:Multiple Choice, Cloze Task, Student’s Reading Comprehension